Моделювання теплової обробки насіння олійних культур високотемпературним теплоносієм - Дідур, Володимир Володимирович; Журавель, Дмитро Павлович; Колесніченко, Ірина Анатоліївна; Петриченко, Євгеній Анатолійович; Didur, Volodymyr; Zhuravel, Dmutro; Kolesnichenko, Iruna; Petrychenko, Yevhenii (Запоріжжя : Видавничій дім "Гельветика", 2025)
UA: Складність прямого вимірювання просторових полів температури та вологовмісту в капілярно-пористих матеріалах зумовлює потребу у фізично обґрунтованих моделях, здатних порівнювати альтернативні режими термообробки та вибирати енергоощадні варіанти з гарантованою якістю продукту. Запропоновано феноменологічну модель нестаціонарного тепломасоперенесення з урахуванням капілярних і поверхневих сил, інтенсивності міжфазного масообміну та термокапілярних течій; модель спирається на рівняння двофазної фільтрації, ізотерми сорбції та термодинамічні співвідношення Кельвіна і Клапейрона – Клаузіуса. Розроблено чисельну реалізацію на основі методу зважених нев’язок (Галеркіна) та показано узгодження з експериментом у межах довірчого інтервалу. Практична цінність – підвищення точності прогнозу волого- та теплообміну й оптимізація режимів сушіння агросировини. /// EN: Recently, during the thermal treatment of grain crops, priority has been given to high-temperature heat carriers, in particular superheated steam, which has a number of significant advantages. This necessitates the creation of new approaches to the analytical solution of existing models in order to obtain more accurate results for the tasks of optimal control of technological parameters of the processes of drying and roasting oilseeds. Intensive temperature regimes when using a high-temperature heat carrier, on the one hand, must remain within the limits of permissible technological properties of the grain, and on the other hand, ensure a reduction in specific heat and energy costs due to increased productivity. Due to the complexity of direct measurements of temperature fields and moisture content in individual seeds, it is fundamentally important to develop a heat and mass transfer model that allows comparing a wide range of hardware and technological schemes of heat treatment and choosing energy-optimal options with guaranteed quality of the dried product. The complexity of direct measurement of spatial fields of temperature and moisture content in capillary-porous materials necessitates the need for physically based models capable of comparing alternative heat treatment modes and selecting energy-saving options with guaranteed product quality. A phenomenological model of unsteady heat and mass transfer is proposed, taking into account capillary and surface forces, interphase mass transfer intensity, and thermocapillary flows; the model is based on the two-phase filtration equation, sorption isotherms, and Kelvin and Clapeyron–Clausius thermodynamic relations. A numerical implementation based on the weighted residual (Galerkin) method is developed and agreement with the experiment within the confidence interval is shown. The practical value is to increase the accuracy of the prediction of moisture and heat transfer and optimize the drying modes of agricultural raw materials.
Modeling of heat treatment of oilcrop seeds with high-temperature heat transfer
Keywords: двохфазна фільтрація; термодинамічні співвідношення; ізотерми сорбції; теплота сорбції; метод Галеркіна; параметрична ідентифікація; верифікація моделі; прогноз якості; сушіння агросировини; енергоефективність; two-phase filtration; thermodynamic relations; sorption isotherms; heat of sorption; Galerkin method; parametric identification; model verification; quality prediction; drying of agricultural raw materials; energy efficiency